Compositionally-graded ferroelectric thin films by solution epitaxy produce excellent dielectric stability - Ruian Zhang; Chen Lin; Hongliang Dong; Haojie Han; Yu Song; Yiran Sun; Yue Wang; Zijun Zhang; Xiaohe Miao; Yongjun Wu; Zhe Ren; Qiaoshi Zeng; et al. (Nature Communications)
Abstract The composition in ferroelectric oxide films is decisive for optimizing properties and device performances. Controlling a composition distribution in these films by a facile approach is thus highly desired. In this work, we report a solution epitaxy of PbZrxTi1−xO3 films with a continuous gradient of Zr concentration, realized by a competitive growth at ~220 °C. These intriguing films demonstrate a frequency-independent of dielectric permittivity below 100 kHz from room-temperature to 280 °C. In particular, the permittivity of the films can be largely regulated from 100 to 50 by slightly varying Zr compositional gradient. These results were revealed to arise from a built-in electric field within the films due to a coupling between the composition gradient and unidirectional spontaneous polarization. Our findings may pave a way to prepare compositionally-graded ferroelectric films by a solution approach, which is promising for practical dielectric, pyroelectric and photoelectric technical applications.